G79(P) Investigation of children with suspected skull fracture – service evaluation at two centres. (27th April 2015) - Stone, K; Lyttle, M
Abstract : Background and aims: Half a million children attend UK Emergency Departments (EDs) due to head injury (HI) annually. Most have a mild HI, but early identification of those with serious traumatic brain injury (TBI) is crucial. The risk of TBI is significantly higher in the presence of a skull fracture. Cranial bone ultrasound (CRUSS) is an emerging investigation to identify or exclude fractures while avoiding radiation burden. We aimed to assess current imaging practice and evaluate CRUSS accuracy to determine whether its use could reduce CT scanning rates. Methods: Retrospective chart review over twelve months at two sites: Site One: Tertiary Paediatric ED Site Two: District General Hospital ED seeing adults and children. All children 0–16 years (except for suspected abuse cases) receiving imaging for HI, identified via radiology electronic databases, were included. Results: 2, 233 and 804 children were seen due to HI at Sites 1 and 2 respectively, of which 26 (1%) and 38 (5%) fulfilled selection criteria. Imaging modality rates are presented in Table 1 . Most received CT; only a small number (4) had CRUSS – of these, all were neurologically stable, two were delayed presentations (≥24 hrs after injury). Site 2 had a higher CT rate overall (1% vs 4%). There were seven delayed presentations at Site 2 – five could have benefited from USS rather than CT if the service was available. Conclusions: CRUSS may have a role in both acute and sub-acute HI, whether as a decision making aid or diagnostic tool. Its accuracy and utility cannot be determined due to the low numbers in this study. However, we have demonstrated that it is being used, and as this use is likely to increase, further prospective research is required to fully determine its role.